Research on modes of plasma generation in low-pressure discharge for themal radiation processes; IOP Conference Series: Materials Science and Engineering; Vol. 81 : Radiation-Thermal Effects and Processes in Inorganic Materials - Koval T. V. Tamara Vasilievna (2015, 2015)
Title screen